Pemetaan Kebutuhan Air Domestik Masyarakat Di Kecamatan Limboto Provinsi Gorontalo - Fadila, Nur; Nurfaika, Nurfaika; Rusiyah, Rusiyah (Geosfera: Jurnal Penelitian Geografi, 2022)
Domestic water has an important role to meet the needs of human life. The need and use of water always increase which is directly proportional to population growth. Limboto Subdistrict has increased every year, causing an increase in population, development and also the need for water is increasing both domestic, agricultural and plantation water needs. For this reason, planning and conservation related to water resources, especially groundwater, is important to study. The formulation or purpose in this paper is to analyze the spatial distribution of domestic water demand in eight villages in Limboto District. The method used in this study is the direct interview method to determine the water needs of the community, domestic water needs are analyzed using the standard calculation method for domestic water needs based on SNI 9-6728.1.202. The results of this study indicate that Hunggaluwa Village and Hutuo Village are areas that have high domestic water needs (QDMI) with a total of 633,477 (L/person/day) and 589,985 (L/person/day) while areas that have domestic water needs (QDMI) very low, namely in Kayu Merah Village with a total of 115,980 (L/person/day).